Results of Modern Mitral Valve Repair in Patients with Marfan Syndrome - Bernhardt, Alexander Martin; Treede, Hendrik; Detter, Christian; Rybczynski, Meike; Sheikhzadeh, Sara; Wagner, Florian Mathias; Kodolitsch, Yskert Von; Reichenspurner, Hermann (The Thoracic and Cardiovascular Surgeon, 2014)
Objectives Mitral valve (MV) regurgitation is a common manifestation in patients with Marfan syndrome (MFS) and is age dependent. Valve pathology shares some features with myxomatous MV disease. Surgical treatment is still being debated and not well characterized in patients with MFS.Patients and Methods We retrospectively evaluated the results of mitral valve repair (MVR) of symptomatic patients with MFS who underwent surgery between January 2004 and April 2011. MFS was diagnosed following the Ghent criteria. MVR was performed in 12 patients. Three patients underwent minimally invasive MVR despite severe thorax deformities. Mean follow-up was 60.1 months (95% CI: 48–72) and was complete.Results Thirty-day mortality was 0%. One patient died because of arrhythmia 66 months after MVR. Transthoracic echocardiography at last visit showed mild mitral regurgitation in one patient (8.3%) and no mitral regurgitation in the remaining patients (91.7%).Conclusion MVR was associated with excellent survival and a low rate of complications. Transthoracic echocardiography showed good results of the repaired valves even years later. Minimally invasive repairs are feasible even in deformed thoraces, lowering the risk for future aortic surgery. Because of excellent mid-term to long-term results, MVR may also be justified in asymptomatic Marfan patients.
Keywords: Marfan syndrome; mitral valve; mitral valve repair; minimally invasive; neochordae; artificial chordae